Economic value of the pest control service provided by Brazilian free‐tailed bats in south‐central Texas. Issue 5 (1st June 2006) - Cleveland, Cutler J.; Betke, Margrit; Federico, Paula; Frank, Jeff D.; Hallam, Thomas G.; Horn, Jason; López, Juan D.; McCracken, Gary F.; Medellín, Rodrigo A.; Moreno-Valdez, Arnulfo; Sansone, Chris G.; Westbrook, John K.; et al.
Abstract : Brazilian free‐tailed bats (Tadarida brasiliensis ) form enormous summer breeding colonies, mostly in caves and under bridges, in south‐central Texas and northern Mexico. Their prey includes several species of adult insects whose larvae are known to be important agricultural pests, including the corn earworm or cotton bollworm (Helicoverpa zea ). We estimate the bats' value as pest control for cotton production in an eight‐county region in south‐central Texas. Our calculations show an annual value of 741 000 per year, with a range of 121 000–1 725 000, compared to a 4.6–6.4 million per year annual cotton harvest.